2017
DOI: 10.1007/s00415-017-8495-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinical and cognitive features of genetically positive ALS patients from the largest tertiary center in Serbia

Abstract: Discovering novel mutations in C9orf72, FUS, ANG, and TDP-43 genes in ALS patients arises necessities for better clinical characterizations of these subjects. The aim is to determine clinical and cognitive profile of genetically positive Serbian ALS patients. 241 ALS patients were included in the study (17 familiar and 224 apparently sporadic). The following genes were analyzed: SOD1, C9orf72, ANG, FUS, and TDP-43. An extensive battery of classic neuropsychological tests was used in 27 ALS patients (22 SOD1 po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…About 1 2% of SALS patients had either SOD1 p.Leu145Phe or C9orf72 repeat expansion. High frequency of p.Leu145Phe mutation in our study and other cohorts from Southern Europe suggests a probable founder effect [17,21]. On the other hand, the frequency of the C9orf72 repeat expansions in the Serbian SALS patients was in agreement with literature data [22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…About 1 2% of SALS patients had either SOD1 p.Leu145Phe or C9orf72 repeat expansion. High frequency of p.Leu145Phe mutation in our study and other cohorts from Southern Europe suggests a probable founder effect [17,21]. On the other hand, the frequency of the C9orf72 repeat expansions in the Serbian SALS patients was in agreement with literature data [22].…”
Section: Discussionsupporting
confidence: 92%
“…One patient was excluded from the study due to neoplasm of the spinal cord since this affected his functionality and course of the disease. All the remaining 153 patients (90 males and 63 females) were screened for two major causative mutations in Serbian ALS patients [17] in two high-risk ALS genes -p.Leu145Phe (c.435G>C, Ensembl transcript SOD1-201 ENST00000270142.10) mutation in the SOD1 gene and the expansion of the GGGGCC repeat in the C9orf72 gene (mutation = [GGGGCC] > 30). Demographic and clinical characteristics of patients are shown in Table 1.…”
Section: Subjectsmentioning
confidence: 99%
“…Patients with L144F have slowly progressive disease with lower limb onset, combined upper and lower motor neuron signs and atypical clinical features, e.g. sphincter and sensory disturbances 8 .…”
Section: Discussionmentioning
confidence: 99%
“…That study found that SOD1 fALS patients were less vulnerable to cognitive dysfunctions than patients with other genetic variants or with a sporadic disease. Most recently, mild executive dysfunctions have been described in SOD1 ALS carriers, 12 but there was no clear indication of the amount of SOD1 patients with a diagnosis of cognitive (ALSci) and/or behavioral (ALSbi) impairment as suggested by the revised Strong et al 2 criteria. To fill this gap, we applied the guidelines for the assessment and diagnosis of ALSci and ALSbi and compared the neuropsychological profiles of a cohort of 14 patients with ALS carrying SOD1 variants to those of 274 patients without genetic variants (SOD1−).…”
Section: Discussionmentioning
confidence: 99%
“…To date, more than 180 different variants in the SOD1 gene account for approximately 10% of familial ALS (fALS), but SOD1 variants are found also in a small percentage of sporadic ALS (sALS). 6 Although it was believed that individuals carrying SOD1 variants were less likely to have significant cognitive changes compared with SOD1 negative fALS patients, 7 sparse clinical evidence (Table 1) suggests that cognitive alterations may not be uncommon also in SOD1 patients, [8][9][10][11][12][13] with rare patients with ALS presenting even cognitive and behavioral decline before motor symptoms' onset. 10,11 Behavioral changes have been described also in the mouse SOD1 model.…”
mentioning
confidence: 99%